2020
DOI: 10.3390/smartcities3020025
|View full text |Cite
|
Sign up to set email alerts
|

Using Smart City Tools to Evaluate the Effectiveness of a Low Emissions Zone in Spain: Madrid Central

Abstract: Population concentration in cities brings new risks as an increase in pollution, which causes urban health problems. In order to address this problem, traffic reduction measures are being implemented as pedestrianization areas; they are the definition of Low Emissions Zones (LEZs). When the effectiveness of these types of measures is in doubt, smart city tools provide data that can be used to scientifically asses their impact. This article analyzes the situation of Madrid Central (Spain), a LEZ subject to cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Platforms integrating 5G connection with blockchain technologies for IoT are also widely discussed solutions in terms of advanced, intelligent, and efficient systems to optimize operations between machines, computers, and people [ 119 , 120 ]. In a broader perspective, the aforementioned solutions would allow the creation of “Smart Cities”, where modern technologies, including IoT, would be combined to solve communication, infrastructure, social, and pollution problems, aiming at improving the quality of life of metropolitan inhabitants [ 121 , 122 , 123 ].…”
Section: Modern Methods For Air Pollution Monitoringmentioning
confidence: 99%
“…Platforms integrating 5G connection with blockchain technologies for IoT are also widely discussed solutions in terms of advanced, intelligent, and efficient systems to optimize operations between machines, computers, and people [ 119 , 120 ]. In a broader perspective, the aforementioned solutions would allow the creation of “Smart Cities”, where modern technologies, including IoT, would be combined to solve communication, infrastructure, social, and pollution problems, aiming at improving the quality of life of metropolitan inhabitants [ 121 , 122 , 123 ].…”
Section: Modern Methods For Air Pollution Monitoringmentioning
confidence: 99%
“…Most of these methods predict the air pollution concentration giving the previous pollution concentration and other external conditions, such as the weather. It has been shown that Urban road mobility affects air quality [22,23]. Thus, different approaches based on ANNs model the air pollution according to the current road traffic density [24].…”
Section: Related Workmentioning
confidence: 99%
“…Some of the most relevant researches and published articles include the energy efficiency studies via computational intelligence for electricity demand forecasting in industrial and residential sectors [9]; IoT developments, such as the proposal of smart bus stops for increasing social inclusiveness and quality of life of elders [10]; electric mobility, such as a power supply solution for electric trains [11]; waste management in modern smart cities [12]; pollution and air quality, such as assessing the effectiveness of low emissions zones [13]; and sustainable mobility in public transportation [14].…”
Section: Research and Developmentmentioning
confidence: 99%